(untitled) (Research, Society and Development, 2022)
The pandemic triggered by new coronavirus in 2020 had several impacts on social sectors, including education. In this scenario, in order to be able to continue teaching-learning process, several educational institutions chose to establish remote education, through adoption of digital resources that enabled this type of teaching. In current pandemic period, monitoring has proved essential to assist teaching-learning process, providing support to teachers and students of the discipline. Thus, the objective was to report experienced from a period of monitoring in Embryology and Histology discipline, of a Federal Institution of higher education located in Paraiba (Brazil), during remote education. With monitoring activity, the academic-monitor participated in several activities of initiation to teaching, such as moments for discussions and clarification of doubts with students about the disciplines contents, indication of bibliographic material as a complementary source of reading, conducting questionnaires through digital platforms, preparation and correction of studies directed by guide, as well as interaction with students through social networks. In addition, the monitor had observed the challenges faced by the preceptor teacher in the teaching process, assisting the teacher and contributing to the improvement of their training as a bachelor degree in Biological Sciences. In this perspective, the monitoring provided a learning environment for both the monitor and the teacher, as well as for the students of the discipline.